2016
DOI: 10.1016/j.neuron.2016.08.037
|View full text |Cite
|
Sign up to set email alerts
|

Spatially Compact Neural Clusters in the Dorsal Striatum Encode Locomotion Relevant Information

Abstract: Summary An influential striatal model postulates that neural activities in the striatal direct and indirect pathways promote and inhibit movement, respectively. Normal behavior requires coordinated activity in the direct pathway to facilitate intended locomotion and indirect pathway to inhibit unwanted locomotion. In this striatal model, neuronal population activity is assumed to encode locomotion relevant information. Here, we propose a novel encoding mechanism for the dorsal striatum. We identified spatially… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

59
369
13

Year Published

2017
2017
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 304 publications
(441 citation statements)
references
References 39 publications
59
369
13
Order By: Relevance
“…How these cellular and network adaptations dictate behavior remains unanswered, but the rapid evolution of in vivo recording techniques that can be applied to awake, unanesthetized animals is sure to provide new insights in the near future. Although it was believed for decades that direct and indirect pathways had opposing effects on behavioral output, a rapidly growing body of evidence suggests that this model is oversimplified — coordinated activity and spatiotemporal organization of neuronal ensembles of both pathways are critical to behavior [90*,9193]. It would be invaluable to determine how these additional dimensions are altered in parkinsonian state.…”
Section: Discussionmentioning
confidence: 99%
“…How these cellular and network adaptations dictate behavior remains unanswered, but the rapid evolution of in vivo recording techniques that can be applied to awake, unanesthetized animals is sure to provide new insights in the near future. Although it was believed for decades that direct and indirect pathways had opposing effects on behavioral output, a rapidly growing body of evidence suggests that this model is oversimplified — coordinated activity and spatiotemporal organization of neuronal ensembles of both pathways are critical to behavior [90*,9193]. It would be invaluable to determine how these additional dimensions are altered in parkinsonian state.…”
Section: Discussionmentioning
confidence: 99%
“…Recent work in the dorsal striatum using calcium imaging with fiber photometry (Cui et al, 2014; Tecuapetla et al, 2014), deep brain calcium imaging (Barbera et al, 2016), and in vivo electrophysiology in which SPN subtypes were identified with optogenetic tagging (Jin et al, 2014) or post hoc in situ hybridization (Isomura et al, 2013), have all demonstrated that both dSPNs and iSPNs are more active when an animal is performing a task or freely moving and less active when the animal is not moving or engaged in a task (though dSPNs and iSPNs have differing activity patterns). These data imply that iSPNs and dSPNs are coactive during action initiation and that the direct and indirect pathways are both necessary to facilitate actions.…”
Section: General Overviewmentioning
confidence: 99%
“…An important question then is how to reconcile the findings from optogenetic stimulation experiments suggesting that iSPN activation inhibits movement (Kravitz et al, 2010) with those from calcium dynamics showing iSPN activation during action initiation and behavior (Barbera et al, 2016; Cui et al, 2014; Natsubori et al, 2017). The most parsimonious explanation is that during behavior, dSPNs facilitate the desired behavior, while iSPNs act simultaneously to inhibit all other competing undesirable behaviors (see more in section 3).…”
Section: General Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…This technique usually requires the insertion of a small graded-index (GRIN) optical lens inside the brain, and has been successfully used to study the function of deep brain structures such as the hippocampus (Okuyama et al, 2016; Ziv et al, 2013), amygdala (Grewe et al, 2017), striatum (Barbera et al, 2016) and hypothalamus (Jennings et al, 2015). However, the cerebral cortex located at the top of the brain has not yet been extensively studied through this technique (Pinto and Dan, 2015).…”
Section: Introductionmentioning
confidence: 99%